Pengaruh Corporate Social Responsibility, Social Media Marketing, Store Environment, dan Perceived Value terhadap Purchase Decision (Studi Kasus Pada Pelanggan Pamella Satu Supermarket Yogyakarta) - Ayang, Anias Ina Aprilia; Udayana, Ida Bagus Nyoman; Maharani, Bernadetta Diansepti (Universitas Batanghari Jambi, 2024)
The study's goal is to examine the effects of corporate social responsibility (CSR), social media marketing (SMM), store ambience, and perceived value on shoppers' decisions at Pamella Satu Yogyakarta. The article analyzes the influence of many external variables, including CSR, SMM, store environment, perceived value, and final purchase decision. Ninety shoppers of Yogyakarta's Pamella Satu Supermarket participated in the study. A random sample approach was used in the distribution of the questionnaire. This study used multiple regression, testing of hypotheses, and checks for data quality as well as tests based on classical assumptions. Corporate social responsibility (CSR) was shown to have a significant beneficial impact on customer buying choices, whereas the effects of social media marketing (SMM) was found to be negative and insignificant. Third, the ambience of a business has a negligible and negative effect on clients' ultimate purchases. The extent to which consumers perceive value influences their purchases is substantial.